Kewenangan Dinas Pemadam Kebakaran dalam Pelayanan Non Kebakaran sebagai Upaya Peningkatan Pelayanan Publik (Studi Di Kabupaten Lima Puluh Kota) - Syukri Anda; Darmini Roza; Philips A. Kana (LPPM Universitas Ekasakti Padang, 2023)
Regional Regulation Number 15 of 2016 Concerning the Formation of Regional Structures and Devices, the Fifty Cities District Fire Service has been independent and has effectively carried out its duties since January 2017 which has the task of providing services, one of which is non-rooted services. The results of the study can be explained that the authority of the Fire Department in Non- Fire Services in Fifty Cities District refers to the Fifty Cities District Regulation Number 4 of 2020, namely: Disaster Victim Rescue, evacuation of threats to life or property, evacuation of animal safety and providing support for governance and community services. Constraints faced by the Fire Service of the Lima Puluh Kota Regency in public services in the field of non-fire services a) lack of impartiality in budgeting policies for the implementation of non-fire services b) lack of optimal utilization of non-fire services by related OPDs. c) there is not yet an understanding between OPDs regarding fire fighting duties in these non-fire services. d) Inadequate information and communication in some villages/communities. f) not all people understand the duties of the Fire Service in non-fire services, g) inadequate performance of fire and disaster management apparatus and institutions, and h) lack of effective coordination. And efforts to overcome the obstacles faced by the Fire Department of the Fifty Cities Regency in public services in the field of non-immortal services are a) increasing budgetary policies, b) unifying understanding between OPDs related to fire fighting duties in non-fire services. c) informing and communicating the authority of firefighters in non-fire services. d) outreach to the public in order to understand the duties of the fire department in non-fire services. e) increasing the number of human resources both in terms of quality and quantity.